Contributions of Behavior Analysis to Behavioral Economics - Furrebøe, Elise Frølich (Behav Anal, 2017)
This article discusses behavior analysis’ contribution to behavioral economics. Nobel Laureate Award winner Herbert Simon described the science of economics in an evolutionary context in A Behavioral Model of Rational Choice. Without claiming any relation between the two publications, it was published two years after B.F. Skinner’s Science and Human Behavior. While popular behavioral economics continues the critique of Homo Economicus, the eagerness to prove that man is not rational carries the risk of substituting one mentalistic explanation for another. Behavior analysis may contribute to developing knowledge about behavioral economics and consumer behavior. The selectionist perspective, the generic principle of reinforcement, and single-subject research are its main contributions. The conceptual framework of behavior analysis enables investigation of the selection of functional relations between human choice behavior and its environmental contingencies. The circumstance-specific research methods of behavior analysis and the possibility to extend them into large-scale analysis provide the means to explain the psychological underpinnings of behavior. Behavior economics offers good descriptions of important phenomena, and behavior analysis contributes with the technology to explain and influence them.